Supplementation of a clay mineral-based product modulates plasma metabolomic profile and liver enzymes in cattle fed grain-rich diets. (17th October 2018) - Humer, E.; Kröger, I.; Neubauer, V.; Reisinger, N.; Zebeli, Q.
Abstract : Grain-rich diets often lead to subacute ruminal acidosis (SARA) impairing rumen and systemic cattle health. Recent data suggest beneficial effects of a clay mineral (CM)- based product on the rumen microbiome of cattle during SARA. This study sought to investigate whether the CM supplementation can counteract SARA-induced perturbations of the bovine systemic health. The study used an intermittent diet-induced SARA-model with eight dry Holstein cows receiving either no additive as control or CM via concentrates ( n =8 per treatment). Cows received first a forage diet (Baseline) for 1 week, followed by a 1-week SARA-challenge (SARA 1), a 1-week recovery phase (Recovery) and finally a second SARA-challenge for 2 weeks (SARA 2). Cows were monitored for feed intake, reticular pH and chewing behavior. Blood samples were taken and analyzed for metabolites related to glucose and lipid metabolism as well as liver health biomarkers. In addition, a targeted electrospray ionization-liquid chromatography-MS-based metabolomics approach was carried out on the plasma samples obtained at the end of the Baseline and SARA 1 phase. Data showed that supplementing the cows' diet with CM improved ruminating chews per regurgitated bolus by 16% in SARA 1 ( P =0.01) and enhanced the dry matter intake during the Recovery phase ( P =0.05). Moreover, the SARA-induced decreases in several amino acids and phosphatidylcholines were less pronounced in cows receiving CM ( P ≤0.10). The CM-supplemented cows also had lower concentrations of lactate ( P =0.03) and biogenic amines such as histamine and spermine ( P <0.01) in the blood. In contrast, the concentration of acylcarnitines with key metabolic functions was increased in the blood of treated cows ( P ≤0.05). In SARA 2, the CM-cows had lower concentrations of the liver enzymes aspartate aminotransferase and γ -glutamyltransferase ( P <0.05). In conclusion, the data suggest that supplementation of CM holds the potential to alleviate the negative effects of high-grain feeding in cattle by counteracting multiple SARA-induced perturbations in the systemic metabolism and liver health.